Knowledge, attitude, and practice of psoriasis patients toward their diseases: a web-based, cross-sectional study - Tian, Jun; Zhang, Lei; Zhao, Xiangrong; Yang, Li (Frontiers in Medicine, 2024)
Objective: To investigate the knowledge, attitude, and practice (KAP) of psoriasis patients towards the disease. Methods: A web-based cross-sectional study was conducted among psoriasis patients who were diagnosed at the outpatient of Shaanxi Provincial People's Hospital in March 2023. A self-designed questionnaire was administered for data collection and KAP assessment. Results: A total of 526 valid questionnaires were included, including 257 males (48.86%) psoriasis patients. Their mean KAP scores were 8.09  3.60 (possible range: 0-12), 31.94  4.61 (possible range: 10-50), and 51.92  8.83 (possible range: 15-75), respectively. Pearson’s correlation analysis showed a positive correlation between knowledge and attitude (r=0.186, p<0.001), a positive correlation between knowledge and practice (r=0.313, p<0.001), and a negative correlation between attitude and practice (r=-0.181, p<0.001). Moreover, structural equation model showed that medication (β=2.74, 95% CI: 2.17, 3.32, p<0.001) has significantly positive effect on knowledge. Education (β=0.56, 95% CI: 0.31, 0.81, p<0.001) and duration of psoriasis (β=1.01, 95% CI: 0.54, 1.49, p<0.001) have significantly positive effect on attitude. Knowledge (β=1.03, 95% CI: 0.80, 1.26, p<0.001) and medication (β=4.59, 95% CI: 2.78, 6.40, p<0.001) has significantly positive effect on practice, while attitude (β=-0.41, 95% CI: -0.57, -0.26, p<0.001) and duration of psoriasis (β=-2.53, 95% CI: -3.49, -1.57, p<0.001) exhibit significantly negative effect on practice. Conclusion: Psoriasis patients have good knowledge, positive attitude, and proactive practice towards the disease. Education, medication, duration of psoriasis might have effect on their KAP.